Wheat Productivity and Soil Physicochemical Response Under Organic vs. Chemical Fertilization - S. B. Bhosale (The Bioscan, 2025)
Wheat is a major staple crop essential for global and national food security, and its productivity is strongly influenced by nutrient management practices. The present study was conducted to compare the effect of organic and chemical fertilization on growth performance, yield attributes, grain productivity and soil physicochemical properties of wheat (Triticum aestivum L.) variety HD-2189. Four nutrient management treatments were evaluated including control (no nutrients), recommended dose of chemical fertilizers (NPK), organic inputs (FYM + vermicompost) and integrated organic inputs combined with biofertilizers (FYM + vermicompost + PSB + Azotobacter). The results indicated that chemical fertilization promoted early vegetative growth and improved grain yield in the initial phase; however, organic fertilization and integrated nutrient management significantly enhanced tiller formation, thousand kernel weight, grain nutritional quality and soil fertility. The integrated organic treatment recorded the highest soil organic carbon, available macro and micronutrients, and superior grain protein and mineral content. In contrast, continuous chemical fertilization showed reduced soil organic carbon and limited improvement in grain quality. The findings suggest that integrated nutrient management practices offer a sustainable approach for maintaining wheat productivity while improving soil health and grain nutritional value over the long term. KEYWORDS: Wheat; Organic Fertilization; Chemical Fertilizers; Soil Fertility; Grain Yield; Nutrient Management; Sustainability.